2013
DOI: 10.1089/brain.2012.0125
|View full text |Cite
|
Sign up to set email alerts
|

Graph Theoretical Analysis of Sedation's Effect on Whole Brain Functional System in School-Aged Children

Abstract: The neurophysiological mechanism underlying sedation, especially in school-aged children, remains largely unknown. The recently emerged resting-state functional magnetic resonance imaging (rsfMRI) technique, capable of delineating brain's functional interaction pattern among distributed brain areas, proves to be a unique and powerful tool to study sedation-induced brain reorganization. Based on a relatively large school-aged children population (n=28, 10.3±2.6 years, range 7-15 years) and leveraging rsfMRI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 88 publications
(129 reference statements)
0
8
0
Order By: Relevance
“…We calculated the global efficiency, local efficiency, and small-worldness. These indices are crucial for understanding the information sharing, integration, and segregation among the brain system 58 . Global efficiency represents the total capacity for parallel processing of information and integrated processing 59 .…”
Section: Methodsmentioning
confidence: 99%
“…We calculated the global efficiency, local efficiency, and small-worldness. These indices are crucial for understanding the information sharing, integration, and segregation among the brain system 58 . Global efficiency represents the total capacity for parallel processing of information and integrated processing 59 .…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, we recognize that sedation may affect brain structure and function. A brain connectivity analysis of resting-state functional MRI study examined the effect of chloral hydrate-induced light sedation in school-aged children (Wei et al, 2013). Their study showed a global detrimental effect of sedation on the functional interactions of the brain, especially on the information-processing properties.…”
Section: Discussionmentioning
confidence: 99%
“…Anesthetics have often been used to gain a better understanding of the clinical relevance of resting‐state fMRI biomarkers (see “Methods Validation and Calibration” for details). Derivative biomarkers such as network properties, coherence or spectral power, have been used to study the global effects of drugs on the brain, in terms of the reconfiguration of resting‐state networks under sedation with propofol [Gili et al, ; Jordan et al, ; Monti et al, ; Schroter et al, ; Schrouff et al, ], chloral hydrate [Wei et al, ] and sevoflurane [Peltier et al, ; Qiu et al, ].…”
Section: Experimental Objectives and Clinical Relevancementioning
confidence: 99%
“…Anesthetics have often been used to gain a better understanding of the clinical relevance of resting-state fMRI biomarkers (see "Methods Validation and Calibration" for details). Derivative biomarkers such as network properties, coherence or spectral power, have been used to study the global effects of drugs on the brain, in terms of the reconfiguration of resting-state networks under sedation with propofol [Gili et al, 2013;Jordan et al, 2013;Monti et al, 2013;Schroter et al, 2012;Schrouff et al, 2011], chloral hydrate [Wei et al, 2013] and sevoflurane [Peltier et al, 2005;Qiu et al, 2008]. As will be discussed in "Challenges and Limitations," dose/response evaluation, also known as pharmacokinetic/pharmacodynamic (PK/PD) modeling is one of the most challenging, but also most important goals of pharmacological neuroimaging.…”
Section: Dose/response In Anesthesiologymentioning
confidence: 99%
See 1 more Smart Citation